2019
DOI: 10.2172/1498258
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of Chemical Additives For Glycolate Destruction In The Recycle Collection Tank

Abstract: Savannah River National Laboratory (SRNL) has completed a work scope in support of the Savannah River Remediation (SRR) Nitric-Glycolic flowsheet. Glycolic acid will replace formic acid as a reducing agent in the pre-processing of High-Level Waste sludge performed at the Defense Waste Processing Facility (DWPF). Glycolic acid will perform the same function as formic acid, namely reduction of mercury and adjustment of feed rheology and melter oxidation/reduction potential, while significantly reducing the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…It was shown that permanganate did not react with methyl mercury. 43 Another test was performed on the effectiveness of permanganate oxidation to destroy glycolate in a sample from the SMECT. 7 Analysis of the initial sample from the SMECT revealed that the methylmercury concentration was below the detection limit, so no information from that test is available on whether there is a reaction between methylmercury and permanganate.…”
Section: Glycolate Destructionmentioning
confidence: 99%
“…It was shown that permanganate did not react with methyl mercury. 43 Another test was performed on the effectiveness of permanganate oxidation to destroy glycolate in a sample from the SMECT. 7 Analysis of the initial sample from the SMECT revealed that the methylmercury concentration was below the detection limit, so no information from that test is available on whether there is a reaction between methylmercury and permanganate.…”
Section: Glycolate Destructionmentioning
confidence: 99%
“…It should be noted that during down select testing using smaller volumes (e.g., 1.8 L) with 10x scale purge rates, no H2 attributed to process was ever detected and CO2 is not expected in caustic conditions. 6 The analysis frequency for the FTIR and GC were <10 seconds and four minutes respectively.…”
Section: Off-gas Analysismentioning
confidence: 99%
“…The third phase of testing was to demonstrate nominal operation of the permanganate oxidation process under protocols similar to those used in the Defense Waste Processing Facility (DWPF). 7 6,7 In addition, equation (1) was found to best describe the observed reaction of glycolate with permanganate under nominal and low glycolate entrainment conditions. 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from these laboratory studies were summarized in a series of reports. [5][6][7][8][9] Tests at caustic conditions demonstrated sodium permanganate was effective in converting glycolate to oxalate, and permanganate (Mn 7+ ) is reduced to manganate (Mn 6+ ) with no significant formation of carbon dioxide or carbonate. Equation (1) was found to best describe the observed reaction of glycolate with permanganate under nominal and low glycolate entrainment conditions.…”
Section: Introductionmentioning
confidence: 99%